Ethical dilemmas of the medical sales representatives in pharmaceutical marketing and sales - Martinez, Cedrick Yves M.; Yango, Antonio R. (Technium Social Sciences Journal, 2023)
This phenomenological study investigated the ethical dilemmas of Medical Sales Representatives (MSRs) in pharmaceutical marketing and sales in the province of Laguna. Specifically, this research utilized transcendental phenomenology and applied triangulation of the three methods: observation, interviews focus group discussion. After executing the identifying the significant statements, bracketing, horizontalization, and theme clustering, the researcher revealed seventeen (17) themes. As to the ethical dilemmas experienced by MSRs in pharmaceutical marketing and sales, the concept branched out to nine thematic concepts of their shared reality. Theme 1: Personal Growth and Professional Development, Theme 2: Product Knowledge and Interpersonal Skills, Theme 3: Be Knowledgeable, Friendly, and Patient, Theme 4: Understanding the Clients' Needs, Preferences, and Interests, Theme 5: Be Focused, Good Communicator, and Compassionate, Theme 6: Flexibility and Opportunity, Theme 7: Rejections and Failure, Theme 8: Satisfaction and Patient-Care, and Theme 9: Effectivity and Affordability. From their shared experiences regarding how the MSRs face ethical dilemmas in pharmaceutical marketing and sales, the researcher developed eight sensible themes: Theme 10: Handling and Dealing with Various Aspects, Theme 11: Keeping Patient with Positive Mindset to Solve the Problems, Theme 12: Learning and Motivation, Theme 13: Helping Consumers to Cure their Illnesses, Theme 14: Keeping the Clients and Building Good Relationships, Theme 15: Disappointed, yet Motivated, Theme 16: Analyze, Strategize, and Improve, and Theme 17: Modernized and Research-Based. The consensus among the participants' statements revealed that there are certain factors, strategies, and solutions that medical sales representatives consider succeeding in the pharmaceutical sector. The MSRs possess good communication skills and product expertise, which are necessary for every MSR and assist them in achieving their target sales, even though becoming one is difficult due to failures and rejections. In addition, effective marketing strategies and analysis must be used to fulfill the company's objectives. To better align their experiences and develop strategies that would make doing business with them easier, future researchers in the field of marketing and sales in the pharmaceutical industry should investigate to learn how healthcare professionals and their institutions perceive medical sales representatives and their organizations.